Development of oral comprehension of the English language through the B-learning blended learning in university students - Andrade Velásquez, Marjorie (Universidad Politécnica Salesiana (Ecuador), 2016)
This research proposes the use of B-learning mode which combines classroom and distance education, retaking the advantages of both modalities to complement and support the development of oral comprehension of the English class students of the fourth level at Catholic University in Santo Domingo. Dokeos, was used for this research which is an educational platform that provides the ability to interact with one or more users for educational purposes. The quasi-experimental design was applied pre - post in an intact group of fortysix students of English. The results show a greater increase in learning, show that most of the students are motivated to use technology positively and observed B -learning methodology to support campus classes.